Pattern of injuries amongst tennis players in Accra, Ghana - Gabriella Acquaye; Jonathan Quartey; Samuel Kwakye (AOSIS, 2020)
Background: Tennis is a popular global sport characterised by repeated, explosive motions and the involvement of several muscle groups during different strokes, which fluctuates randomly from brief periods of maximal or near maximal work to longer periods of moderate and low intensity activity. Objectives: To determine the pattern of injuries amongst tennis players in Accra. Method: A cross-sectional study was conducted, involving 142 male and female participants selected from tennis clubs in Accra and the Accra sports stadium. A standardised tennis injury report form was used to obtain data from participants. Data on the parts of the body mostly injured and the types of injury mostly sustained by the players were summarised and presented appropriately with the use of graphs and pie charts. Assessment of the causes underlying the prevailing injuries to tennis players was also tabulated and comparisons made. Results: Out of a total of 170 injuries recorded, knee (39 [27.5%]) and shoulder (31 [21.1%]) injuries were the most commonly sustained. Most (80 [56.3%]) tennis injuries occurred during training. Other injuries (26 [18.3%]) occurred during competitions or tournaments whilst 26 (18.3%) occurred during social play. About 10 (7.0%) participants were not certain of the type of activity at the time of injury. The majority (35 [24.65%]) of the players received no treatment for their injuries. However, few of the injuries (20 [14.08%], 14 [9.86%], 6 [4.23%]) sustained were treated by medical personnel, physiotherapists or nurses respectively. There was no association between warm-up before play and cause of injury (p = 0.375). There was also no association between shoe type and cause of injury (p = 0.253). Conclusion: The majority of the injuries occurred in the upper and lower limbs. Most of these injuries occurred during training with overuse and overexertion being the most common cause. Clinical implications: It is important to educate tennis players and coaches on injury prevention measures and the use of protective gear during tennis.